Pengaruh Kompetensi dan Disiplin Kerja terhadap Kinerja Pegawai : Studi Kasus Pada Salah Satu Instansi di Kota Bandung - Fitri Aryani; RD Okky Satria; Adhie Fasha Nurhadian; Aan Hardiyana (Acman: Accounting and Management Journal, 2022)
Researchers researched to determine the effect of Competence and Work Discipline on the Performance of Regional Office Employees III of the Bandung City State Civil Service Agency. Furthermore, this research analyzes the factor that has the most dominant influence between Competency and Work Discipline on the Performance of Employees at the Regional Office III of the State Personnel Agency for the City of Bandung. Based on path analysis research, the competency and discipline variables on the performance of employees of the Regional Office of the Bandung City State Civil Service Agency are declared valid. Therefore, the conclusions and considerations related to the research results are paying attention to Competency and Work Discipline to Improve Employee Performance. The results of the study show that compensation (X1) has a significant effect on employee performance (Y). Likewise, Work Discipline (X2) significantly influences Employee Performance (Y). Competence (X1) and Work Discipline (X2) have a positive influence on Employee Performance (Y). Based on research results, companies need to improve programs such as training and seminars that support optimizing competence to increase employee performance. In addition, companies need to reinforce the applicable rules and sanctions so that work discipline is optimal. If the employee is disciplined, the employee's performance will increase. Based on the results of company research, it is better to improve employee performance, then competence and work discipline need to be optimized and improved.